Towards Model of Community Economic Empowerment through Tourism Activities in Bogor Regency, West Java, Indonesia - Pradono, Pradono; Faisal, Budi; Adriani, Yani; R., Rikeu; Fajriasanti, R. (International Journal of Economics and Financial Issues, 2016)
The root of the problems in Puncak area is the least tourism products developed in accordance with the sustainable principles. Local tourism actors and entrepreneurs engaged in tourism tend to offer modern man-made tourism facilities and less concern with local resources. This paper aims at attempting to find patterns or models of economic empowerment through tourism in a rural setting. Through a series of discussion at the level of decision maker and the village communities in 3 sub districts, we explore, analyze and propose the most acceptable arrangement for economic empowerment in the 3 selected villages. The proposed model is agreed and will be implemented for the next year government budget for a pilot project with various stakeholders’ supports. It is expected the model is able to accelerate rural economic development, and the expansion of tourism businesses are managed in a sustainable manner. Keywords: model, community, economic empowerment, tourism JEL Classifications: O35; R11; Z32